Eye movement-related brain activity during perceptual and cognitive processing - Andrey R. Nikolaev (Frontiers Research Topics, 2014)
The recording and analysis of electrical brain activity associated with eye movements has a history of several decades. While the early attempts were primarily focused on uncovering the brain mechanisms of eye movements, more recent approaches use eye movements as markers of the ongoing brain activity to investigate perceptual and cognitive processes. This recent approach of segmenting brain activity based on eye movement behavior has several important advantages. First, the eye movement system is closely related to cognitive functions such as perception, attention and memory. This is not surprising since eye movements provide the easiest and the most accurate way to extract information from our visual environment and the eye movement system largely determines what information is selected for further processing. The eye movement-based segmentation offers a great way to study brain activity in relation to these processes. Second, on the methodological level, eye movements constitute a natural marker to segment the ongoing brain activity. This overcomes the problem of introducing artificial markers such as ones for stimulus presentation or response execution that are typical for a lab-based research. This opens possibilities to study brain activity during self-paced perceptual and cognitive behavior under naturalistic conditions such as free exploration of scenes. Third, by relating eye movement behavior to the ongoing brain activity it is possible to see how perceptual and cognitive processes unfold in time, being able to predict how brain activity eventually leads to behavior. This research topic illustrates advantages of the combined recording and analysis of eye movements and neural signals such as EEG, local field potentials and fMRI for investigation of the brain processes in humans and animals. The contributions include research papers, methodology papers and reviews demonstrating conceptual and methodological achievements in this rapidly developing field.